trategy of Fast Fashion Retailers in the Czech Republic - A Case Study Analysis of Three Chosen Retailers - Kučmašová, Hana (2010)
The aim of this master thesis is to define fast fashion and fast fashion retailing, and describe specifics of their business activities with deep focus on the Czech market. The theoretical part reviews literature dealing with international strategy and management and fashion and fast fashion retailing. The empirical part then focuses on real-life business cases. In order to illustrate the behaviour of fast fashion retailers on the Czech market, a case study method is employed. The attention is narrowed on three chosen fast fashion retailers MANGO, Zara and H&M. The separate case studies on MANGO, Zara and H&M focus on retailers' presence in the Czech market. The retailers' position on the market and strategies are then compared with the aim to identify the most successful fast fashion retailer and verify whether the hypothesis that the first mover to the market gains the competitive advantage is true for the chosen fast fashion retailers in the Czech market. Further, the work tries to find possible factors of the retailers' success in the Czech market.